2021
DOI: 10.1126/scitranslmed.abg0809
|View full text |Cite|
|
Sign up to set email alerts
|

Alpelisib administration reduced lymphatic malformations in a mouse model and in patients

Abstract: Alplesib exerts therapeutic effects in a mouse model of lymphatic anomalies and in six patients with lymphatic malformations over 6 months’ treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 29 publications
3
57
0
1
Order By: Relevance
“…Alpelisib treatment-induced clinical responses in all patients, including improvement of cardiac EF as seen in our index patient. Of note, alpelisib-induced responses in patients who did not respond to prior treatment with mTOR inhibitors, such as rapamycin, similar to observations in KRAS -mutant oncology patients ( Di Nicolantonio et al, 2010 ), similar to the recent findings of Delestre et al ( Delestre et al, 2021 ). Small clinical series have shown that mTOR inhibition can induce responses in a subset of unselected advanced LMs, with observed response rates of ~50–60% ( Freixo et al, 2020 ).…”
Section: Discussionsupporting
confidence: 86%
“…Alpelisib treatment-induced clinical responses in all patients, including improvement of cardiac EF as seen in our index patient. Of note, alpelisib-induced responses in patients who did not respond to prior treatment with mTOR inhibitors, such as rapamycin, similar to observations in KRAS -mutant oncology patients ( Di Nicolantonio et al, 2010 ), similar to the recent findings of Delestre et al ( Delestre et al, 2021 ). Small clinical series have shown that mTOR inhibition can induce responses in a subset of unselected advanced LMs, with observed response rates of ~50–60% ( Freixo et al, 2020 ).…”
Section: Discussionsupporting
confidence: 86%
“…In a recent proof‐of‐concept study, Delestre et al 19 demonstrated the efficacy of alpelisib in a genetic mouse model. Based on these very promising results, they decided to administer the drug to three children and three adults with severe lymphatic malformations secondary to a PIK3CA mutation.…”
Section: Figurementioning
confidence: 99%
“…We present the rst AUC and primary PK parameters in children. Currently, alpelisib dosing in pediatrics is based on a xed-dosing strategy irrespective of weight and age (2-18 years old: 50 mg daily oral dose) (13,14). As weight represents the main determinant of drug exposure in children( 16), weight-adjusted dosing was chosen.…”
Section: Discussionmentioning
confidence: 99%